Metformin and Covid-19: a systematic review of systematic reviews with meta-analysis - Petrelli, Fabio; Grappasonni, Iolanda; Nguyen, Cuc Thi Thu; Tesauro, Marina; Pantanetti, Paola; Xhafa, Sonila; Cangelosi, Giovanni (Acta Biomedica Atenei Parmensis, 2023)
AbstractIntroduction: the COVID-19 infection, caused by severe Coronavirus 2 syndrome (Sars-Cov-2), immediately appeared to be the most tragic global pandemic event of the twentieth century. Right from the start of the pandemic, diabetic patients treated with metformin experienced a reduction in mortality and complications from COVID-19 compared to those with different treatments or no treatment.Objective The main objective of the study was to observe the effects of metformin in hospitalized subjects infected with COVID-19. Specifically, the outcomes of hospitalization in Intensive Care Units or death were examined.Materials and Methods A specific research PICOS was developed and the Pubmed, Embase and Scopus databases were consulted down to April 30, 2022. To estimate the extent of the metformin effect and risk of severity in SARS-CoV-2 infection, the Odd Ratio (OR) with 95% Confidence Interval (CI) published by the authors of the selected systematic reviews was used.Results from five systematic reviews 36 studies were selected. The final meta-analysis showed that thanks to treatment with metformin, DM2 patients affected by COVID-19 had protection against risk of disease severity, complications (ES 0.80; 95% CI) and mortality (ES 0.69; 95% CI).Conclusions More in-depth studies on the use of metformin, compared to other molecules, may be required to understand the real protective potential of the drug against negative outcomes caused by COVID-19 infection in DM2 patients.